Analysis of the Pseudo-Thinking Process of Field-Dependent 8th-Grade Students at SMP Negeri 2 Palu in Solving Pythagorean Theorem Problems - wianita selviani; Mubarik Mubarik; Pathuddin Pathuddin; Alfisyahra Alfisyahra (JURNAL PENDIDIKAN MATEMATIKA, 2026)
The occurrence of pseudo-thinking processes in mathematics learning remains prevalent, as many students solve problems by relying on memorized procedures rather than understanding the underlying concepts. While previous research has largely focused on error analysis or general problem-solving abilities, studies specifically examining pseudo-thinking processes among field-dependent students when solving Pythagorean theorem problems remain limited. This study aims to analyze the pseudo-thinking processes of eighth-grade students at SMP Negeri 2 Palu specifically those with a field-dependent cognitive style while solving Pythagorean theorem problems, by examining the relationship between cognitive style characteristics and pseudo-thinking processes. A descriptive qualitative approach was employed. Data were collected from a single student, purposively selected to represent the field-dependent cognitive style, using the Group Embedded Figures Test (GEFT), a Pythagorean theorem problem-solving test, and semi-structured interviews. Data analysis followed the interactive model proposed by Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing/verification. The results indicate that the field-dependent student exhibited "correct pseudo-thinking" during the planning and execution stages of the solution. This was characterized by the use of procedures based on prior learning experiences and provided examples, lacking support from deep conceptual understanding. However, during the review stage, the subject was able to verify the solution, meaning the characteristics of pseudo-thinking were no longer present. These findings demonstrate that cognitive style plays a role in shaping students' thinking processes during mathematical problem-solving and provide a basis for teachers to design instruction that accounts for students' cognitive style characteristics to enhance conceptual understanding.. Keywords: Pseudothinking, Cognitive Style, Field-Dependent, Pythagorean Theorem.